PhD dissertations in History, 2010-2018: a historiographical survey - Cardoso, José Luís (2021)
This contribution serves as an introduction and framework for the specific analyzes included in this dossier on the doctoral theses concluded in Portugal, from 2010 to 2018, in the various historiographic subdomains. In addition to explaining the methodological approach and the criteria used in this historiographic survey, it also seeks to elucidate the institutional conditions that made possible the dynamism of doctoral training in History in the last 10 years. Despite this positive evolution, attention is drawn to a declining trend in the number of theses carried out in the final 2 years of the period under analysis.